Pengaruh akuntanbilitas, transparansi dan peran perangkat desa dalam pengelolaan Anggaran Pendapatan dan Belanja Desa (APBDes) Kecamatan Juwiring - Saputra, Rendi; Darmanto, Darmanto; Ningsih, Suhesti (Nur Science Institute, 2022)
This study aimed to determine the effect of accountability, transparency, and the role of village officials together and individually on the management of village revenue and expenditure budget in Juwiring District, Klaten Regency. The population used in the study was employees who worked in 19 village offices throughout Juwiring District, Klaten Regency. The research samples were 95 respondents. Withdrawal of samples in this study using purposive sampling techniques. The data analysis method used in this study is multiple linear regression. The test results show that accountability, transparency, and the village apparatus's role simultaneously affect the Village Budget's management (APBDes). Accountability and transparency significantly positively affect managing the Village Budget (APBDes). At the same time, the role of the village apparatus has no significant effect on managing the Village Budget and Expenditure Budget (APBDes) in the Juwiring District, Klaten Regency.